EFEKTIVITAS KONSELING KELOMPOK TEKNIK BIBLIOKONSELING UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS X TBSM 1 DI SMK NEGERI 2 JEMBER - Fakhruddin Mutakin; Amin Fadholi; Arifin Nur Budiono (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Research on the Effectiveness of Group Counseling Bibliocounseling Techniques to Increase the Self-Confidence of Class X TBSM 1 Students at SMK Negeri 2 Jember for the 2021/2022 academic year with 4 students as respondents from a total population of 30 students who were taken using a purposive sampling technique, namely a sampling technique with certain considerations (with moderate, low, very low confidence criteria based on initial data). The methods used in this study are observation, interviews, questionnaires. Data analysis used the t-test formula with the help of SPSS 2022, based on the results of a questionnaire distributed to class X TBSM 1 SMK Negeri 2 Jember for the 2021/2022 academic year. Based on the results of research on the effectiveness of group counseling bibliocounseling techniques to increase self-confidence with the results of the t-test stated that sig 0.02 < α 0.05. This shows that students' self-confidence is in a positive position, meaning that the major hypothesis (Ha) in this study is accepted. Thus the conclusion is obtained: The results of this study stated that there was effectiveness of group counseling in the bibliocounseling technique to increase students' self-confidence. In accordance with the formulation of the problem in this study with the calculation of the t-test in SPSS 2022. It can be seen from the results of the post-test scores which increased after participating in group counseling on the bibliocounseling technique. In this thesis also provides suggestions for the perfection of further research and closing is the end of the research report of this thesis.